The archaic ilial morphology of an enigmatic pipid frog from the upper Pleistocene of the South American pampas - Baez, Ana Maria (2012)
Pipids are odd-looking frogs with a derived morphology that has been considered to be the result of a successful adaptation to a fully aquatic lifestyle. This monophyletic group comprises 33 extant species arranged in three clades mainly distributed in tropical regions of northern South America (Pipa) and sub-Saharan Africa (Xenopodinae and Hymenochirini). Their fossil record, however, documents greater diversity and wider distribution in South America in the Cretaceous and Paleogene. Recently, isolated postcranial bones bearing distinctive pipid features have been collected from Pleistocene beds in Argentina, nearly 2000 km farther south than their present distribution on the continent. Here, we describe a well-preserved pipid ilium possessing features unknown in the living taxa. The fossil is from a new Lujanian (late Pleistocene) locality of the Pampean Region, thereby confirming the intriguing presence of this group in southern South America. We provide a detailed anatomical evaluation of the adult iliac morphology of pipimorphs and use these data, along with molecular data, in a parsimony analysis of living and extinct pipoid taxa to estimate the relationships of the new material. This analysis places the fossil as a stem xenopodine in an unresolved polytomy together with Xenopus romeri from the upper Paleocene-lower Eocene of Brazil and two taxa from the Eocene of Patagonia. These Pleistocene pipid records in the Pampean region and subsequent disappearance may reflect latitudinal shifts owing to the rapid climate changes related to the glacial/interglacial cycles.